Retrospective Multicentric Study on Campylobacter spp. Bacteremia in France: The Campylobacteremia Study . (26th November 2021) - Tinévez, Claire; Velardo, Fanny; Ranc, Anne Gaëlle; Dubois, Damien; Pailhoriès, Hélène; Codde, Cyrielle; Join-Lambert, Olivier; Gras, Emmanuelle; Corvec, Stéphane; Neuwirth, Catherine; Melenotte, Cléa; Dorel, Marie; et al.
Abstract: Background: Campylobacter spp. bacteremia is a severe infection. A nationwide 5-year retrospective study was conducted to characterize its clinical features and prognostic factors. Methods: The study included patients with Campylobacter spp. bacteremia diagnosed in 37 French hospitals participating in the surveillance network of the National Reference Center for Campylobacters and Helicobacters, from 1 January 2015 to 31 December 2019. The goal was to analyze the effects of a delay of appropriate antibiotic therapy and other risk factors on 30-day mortality rates, antibiotic resistance, patient characteristics, and prognosis according to the Campylobacter species. Results: Among the 592 patients, Campylobacter jejuni and Campylobacter fetus were the most commonly identified species (in 42.9% and 42.6%, respectively). The patients were elderly (median age 68 years), and most had underlying conditions, mainly immunodepression (43.4%), hematologic cancers (25.9%), solid neoplasms (23%), and diabetes (22.3%). C. jejuni and Campylobacter coli were associated with gastrointestinal signs, and C. fetus was associated with secondary localizations. Among the 80 patients (13.5%) with secondary localizations, 12 had endocarditis, 38 vascular, 24 osteoarticular, and 9 ascitic fluid infections. The 30-day mortality rate was 11.7%, and an appropriate antibiotic treatment was independently associated with 30-day survival (odds ratio, 0.47 [95% confidence interval, .24–.93]; P  = .03). The median efficient therapy initiation delay was quite short (2 days [interquartile range, 0–4 days]) but it had no significant impact on the 30-day mortality rate ( P  = .78). Conclusions: Campylobacter spp. bacteremia mainly occurred in elderly immunocompromised individuals with variable clinical presentations according to the species involved. Appropriate antimicrobial therapy was associated with improved 30-day survival. Abstract : Campylobacter spp. bacteremia had a rather high early mortality rate but was improved by an appropriate antimicrobial therapy. Secondary localizations were frequent, mainly because Campylobacter fetus supported the need for more systematic screening, particularly for endovascular infections.